THE IMPORTANCE OF FORMING A HEALTHY LIFESTYLE IN PRIMARY CLASS STUDENTS - Hamidova Muxtasarxon To‘xtasin qizi,; Sobirova Jumagul Nomozboy qizi, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The issue of bringing up a mature generation, scientifically justifying the spiritual and moral impact of a healthy lifestyle in the development of social relations, scientific analysis and study of lifestyle due to independence has become an urgent topic. Due to the national independence, to modernize the country and create decent living conditions for the population, increase the diversity and develop the work of shaping a healthy lifestyle in the future generation.